2011
DOI: 10.1007/s11934-011-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Upper Urinary Lithiasis in Patients Who Have Undergone Urinary Diversion

Abstract: Patients undergoing urinary diversion are at high risk for developing stone disease due to the metabolic and structural features intrinsic to the creation of a urinary reservoir. The utilization of shockwave lithotripsy as well as antegrade and retrograde endoscopic techniques in appropriately selected patients affords a relatively safe and effective means of stone removal. This review focuses on the etiology of stone formation in patients with urinary diversion and examines the most relevant and current repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…On the other hand, Seth et al ( 12 ) reported higher rates of complications (such as steinstrasse) after SWL rather than other endourologic procedures. Furthermore, retreatment rates of SWL are considerably high ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Seth et al ( 12 ) reported higher rates of complications (such as steinstrasse) after SWL rather than other endourologic procedures. Furthermore, retreatment rates of SWL are considerably high ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contributing factors for developing stones in urinary diversion have not yet been completely understood and seem to be complex and multifactorial. 3 , 4 Regarding the literature, structural, metabolic, and infectious factors are mentioned. 1–4 Recently described risk factors of stone formation in patients with urinary diversion are urinary stasis because of a high postvoiding residual volume, urinary tract infections with urea splitting organisms, encrustation and stone formation on foreign bodies (e.g., ureteral stents and suture), excessive mucus production, or a chronic metabolic acidosis because of electrolyte imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…These patients usually tend to develop magnesium ammonium phosphate (struvite) and calcium phosphate stones. 3 Lindsay et al postulated that stone analysis of patients with an ileal conduit revealed struvit and calcium phosphate stones as most common findings with 64% and 25%, respectively. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It affects 10% of the population in industrialized countries [1]. It is characterized by the formation of crystalline concretions developing in a basin and/or calyxes of kidney and causing partial or total obstruction to the normal urine flow [2]. Several factors can be linked to the formation of these calculi such as sex, ethnic group, food intake, genetics, climatic aspects, and metabolic disturbances [3].…”
Section: Introductionmentioning
confidence: 99%